Comparative study of surface modification and D retention between beryllium and beryllides under high flux plasma exposure. (June 2021) - Miyamoto, M.; Sugimoto, Y.; Nishijima, D.; Baldwin, M.J.; Doerner, R.P.; Zaloznik, A.; Kim, J.H.; Nakamichi, M.
Highlights: The microstructure and D retention of Be and beryllides, Be12 Ti and Be12 V were investigated. Cone structures form on the Be surface exposed to the plasmas by sputtering. The amorphous layer is induced on the surface of beryllides, which might effectively trap D. The surface enrichment of Ti or V on beryllides occurs due to preferential sputtering of Be. Beryllides exposed to the D + 10%He plasma show lower total retentions of D than in Be. Abstract: The microstructures and deuterium (D) retention properties were investigated for beryllium intermetallic compounds (beryllides), such as Be12 Ti and Be12 V, compared to pure beryllium (Be), exposed to high density pure D and helium (He) mixed plasmas. TEM cross-sectional observations revealed the formation of cone structures on the Be surface exposed to the plasmas at a moderate temperature of 573 K. The crystal structure of the cones and the mass loss caused by the plasma exposure implied that the cone structures were generated by sputtering. The Ti or V surface enrichment was observed on both beryllides with no cone structures developed. TDS measurements indicated that He seeding to D plasma caused a 4 times reduction of the D retention for both beryllides, while no reduction was observed for Be. As a result, the beryllide samples exposed to D + He mixture plasmas showed a lower total D retention than in Be.